Role of district health management teams in child health strategies. (30th July 2018) - Doherty, Tanya; Tran, Nhan; Sanders, David; Dalglish, Sarah L; Hipgrave, David; Rasanathan, Kumanan; Sundararaman, Thiagarajan; Ved, Rajani; Mason, Elizabeth
Abstract : Well functioning district health systems are essential for planning and implementation of health services, and their efforts are key to improving quality of care and achieving health goals, say Tanya Doherty and colleagues